Aphid predators in citrus crops: the least voracious predators are the most effective - Bouvet, Juan Pedro Raúl; Urbaneja, Alberto; Monzó, César (Springer Verlag, 2020)
Rich and abundant predator complexes are frequently associated with aphids in perennial agroecosystems. The ability of these predators to successfully suppress aphid populations is nevertheless highly variable. The development of operative conservation biological control strategies is mostly hindered by the lack of knowledge of the specific roles of the aphidophagous assemblage components, their intra-guild relationships and the predatory attributes that chiefly determine their effectiveness. The role of predation in the biological control of aphids in perennial agroecosystems was assessed through exclusion experiments in aphid infested citrus crops. Important predator attributes such as recruitment, aphid consumption rates, and foraging strategies were related to their efficacy. Predation greatly affected aphid colony phenology as well as size. Predators with lower aphid consumption rates (Micro-coccinellid species and Cecidomyiidae) were revealed to be the most efficient aphidophaga. These predators encountered aphid colonies at earlier colony stages and significantly reduced their population growth rates. Later more voracious aphidophaga groups (Chrysopidae and Macro-coccinellids) did not present effective biological control of the colonies. Contrarily to what was widely believed, the less voracious aphidophaga groups such as the Micro-coccinellids and Cecidomyiids are probably the groups who are mostly responsible for aphid suppression. Future conservation biological control studies in this crop should therefore chiefly focus on these groups.